Змістотвірна функція цитати в сучасній українській поетичній мові - Сюта, Галина; Syuta, Galyna (Східноєвропейський національний університет імені Лесі Українки, 2015)
У контексті теоретичного обґрунтування та побудови практично-аналітичної моделі функціональності цитат, зафіксованих у сучасній українській поетичній мові, охарактеризовано й проілюстровано зміcтотвірну функцію цитатних висловлень у її персуазивно-підтверджувальному та заперечному виявах. In the context of the theoretical studying and constructing of verified linguistic practical-and-analytical model of the functionality of quotations in the modern Ukrainian language poetry of twentieth century, the cases of realization of content-creative function of quotes were characterized and clearly illustrated in its two main forms – confirming and denying. It is proved that for modern Ukrainian authors’ idiosystems revealing expression of their own positions by appealing to the authority of predecessors or denying it. In any case it involves dialogical relations between textes and the maintenance of the unity linguocultural space.
Confirmative Function of Quotes in Contemporary Ukrainian Poetic Language
Keywords: цитата; змістотвірна функція цитати; персуазивна (підтверджувальна) функція цитати; заперечна функція цитати; quote; content-creative function of quotes; confirmative function of quotes; denying function of quotes